USING SHORT STORIES TO IMPROVE STUDENTS’ READING COMPREHENSION AT SENIOR HIGH SCHOOL - Reni Safitri; Muhamad Yahrif; Sukmawati; Muliaty Ibrahim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the impact of using the Busun application on improving the vocabulary skills of tenth-grade students at SMAN 23 Makassar in the 2024/2025 academic year: This research design used a quasi-experimental method with a quantitative approach. The sample was 60 students, consisting of 30 students in the control class and 30 students in the experimental class. This study used a pre-test and post-test, followed by treatment over four meetings. The control class used textbooks as learning media, while the experimental class used the Busuu application. The research data were obtained from the pre-test and post-test results, which were analyzed to determine the improvement in students' vocabulary skills. The results showed that the average pre-test score of students in the control class was 62.93 and the post-test was 70.93, while the average pre-test score in the experimental class was 62.93. The experimental class's average score was 56.67, and the post-test score was 80.53. There was a significant increase in the experimental class's average score of 23.86 after the treatment compared to the control class. The t-test results showed a value of 0.004 < 0.05, therefore, Ho was rejected and Ha was accepted. Based on the results of this study, it can be concluded that the use of the Busu application as a Technology-Based Learning has an effect on improving the vocabulary of 10th-grade Merdeka 2 students at SMAN 23 Makassar.